Integrated farming system approach for enhanced farm productivity, climate resilience and doubling farmers’ income - SINGH, V K; RATHORE, S S; SINGH, R K; UPADHYAY, PRAVIN K; SHEKHAWAT, KAPILA (The Indian Journal of Agricultural Sciences, 2020)
Indian agriculture is plagued by several complex challenges like declining factor productivity, poor resource use efficiency, lesser share in Indian economy (14.4%); high dependence of population on agriculture and allied sectors (52%); more thrust on annual cereal crop production etc. Nearly, 86% of the Indian farmers are small and marginal (<1.0 ha) for whom agriculture has become cost-intensive due to escalating prices of agro-inputs, labour and energy. The decreasing land holding size poses another serious challenge to the profitability and sustainability of Indian agriculture. Achieving economic sustainability in such agricultural production system necessitates coherent linkage of climate-smart agriculture with the farmer’s needs. In this context, integration of cropping with other farming enterprises under integrated farming system (IFS) can ensure enhanced system productivity, resource-use efficiency and more employment opportunities. Research evidences across the country clearly reveals that the complementary co-existence of farm enterprises under IFS can provide an array of benefits in meeting out the growing demands for food and nutrition rich dietary, income stabilization and livelihood upliftment while conserving ecological balance and environmental, particularly for small holders with limited resources. The present review is a synthesis of studies made in different agro-ecologies to explore the potentialities for resource integration in a systems perspective, the implementation feasibility and potential barriers in adoption of a more productive, competitive, diversified and sustainable IFS.